Synergistic photovoltaic–thermoelectric effect in a nanostructured CdTe/Bi2Te3 heterojunction for hybrid energy harvesting. Issue 115 (7th December 2016) - Luo, Bingwei; Deng, Yuan; Wang, Yao; Gao, Min; Zhu, Wei; Hashim, Hasan Talib; García-Cañadas, Jorge
Abstract : A synergistic photovoltaic and thermoelectric effect takes place in a single heterojunction solar cell that consists of a p-type CdTe nanorod array and n-type Bi2 Te3 nanostructures. Abstract : Recent advances in the photovoltaic and thermoelectric material synthesis and characterization have engendered significant interest in their solar energy harvesting. However, examples of energy harvesting by the two effects in one single cell are relatively rare, and at present there are no known examples to solve the heat problem in a conventional solar cell. Here we show that a synergistic photovoltaic and thermoelectric effect takes place in a single heterojunction solar cell that consists a p-type CdTe nanorod array and n-type Bi2 Te3 nanostructures. This novel cell is capable of converting light and heat into electricity via combined photovoltaic and thermoelectric processes, providing a simple and elegant material structure for development of high efficiency solar cells which can harvest solar energy over a wider solar spectrum. In addition, this discovery may provide a viable solution to the heat problems in conventional solar cells. Based on the synergistic photovoltaic and thermoelectric effect, the cell of FTO/CdS/CdTe/Bi2 Te3 has been prepared and an efficiency ( η ) increase of 23.3% is achieved after 1 min illumination.